A NOVEL TECHNIQUE SINGLE SITE MULTIPUNCTURES SUPINE PCNL: CASE SERIES REPORT - Ilham, Muhammad; Satyagraha, Paksi; Kustono, Andri (Indonesian Urological Association, 2024)
Objective: To presents a case series of three patients who received PCNL during 2020 and 2021. Case(s) Presentation: We reported three cases of two females and one male, aged 54, 63, and 48. All patients were diagnosed for having the staghorn stones in the kidney. We performed the “Single Site Multipuncture Supine (SMS) PCNL” technique on these patients. Discussion: Percutaneous Nephrolithotripsy (PCNL) is the preferred surgical technique for treating staghorn or other complicated kidney stones. There are many techniques and modified positions available for PCNL. This technique removes complex kidney stones by making a one cm skin incision to accommodate multiple punctures to access all kidney poles. The highest reduction in hemoglobin was only 1.54 g/dL in the patient who got four punctures, no blood transfusion was needed during post-operative recovery, and no complications occurred during the follow-up period. All patients were stone-free post-operatively without any need for additional procedures. The mean time of overall surgery was 130 minutes. Conclusion: This single-site multi-punctures supine PCNL technique could give the advantage to cosmetics due to less tissue injury. Keywords: Multi punctures, PCNL, staghorn stones.